The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1371/journal.pone.0040143
|View full text |Cite
|
Sign up to set email alerts
|

Osteocyte Network; a Negative Regulatory System for Bone Mass Augmented by the Induction of Rankl in Osteoblasts and Sost in Osteocytes at Unloading

Abstract: Reduced mechanical stress is a major cause of osteoporosis in the elderly, and the osteocyte network, which comprises a communication system through processes and canaliculi throughout bone, is thought to be a mechanosensor and mechanotransduction system; however, the functions of osteocytes are still controversial and remain to be clarified. Unexpectedly, we found that overexpression of BCL2 in osteoblasts eventually caused osteocyte apoptosis. Osteoblast and osteoclast differentiation were unaffected by BCL2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(114 citation statements)
references
References 54 publications
5
104
1
4
Order By: Relevance
“…Subsequently glutamate signalling has been identified as a key signalling pathway potentially regulating bone responses to mechanical loading (30) . Of the other 5 loci Nielson et al identified as being associated with vBMD, WNT4 is also reported to be mechanosensitive, being upregulated within the developing joint line in embryonic mice lacking skeletal muscle (31) , osteoprotegerin(OPG) (coded for by TNFRSF11B) expression is reduced by mechanical loading in osteoblasts in mice (32) , and TNFSF11/RANKL expression in osteoblasts is reportedly increased by unloading (33) . The suggestion that genetic variation in genes involved in skeletal responses to mechanical loading contribute to lumbar spine vBMD, complements findings presented by Yau et al implying that muscle loading, via paraspinal muscle function, contributes to spinal curvature (see Figure 1).…”
Section: Lumbar Spinal Volumetric Bmd; Novel Genetic Variantsmentioning
confidence: 99%
“…Subsequently glutamate signalling has been identified as a key signalling pathway potentially regulating bone responses to mechanical loading (30) . Of the other 5 loci Nielson et al identified as being associated with vBMD, WNT4 is also reported to be mechanosensitive, being upregulated within the developing joint line in embryonic mice lacking skeletal muscle (31) , osteoprotegerin(OPG) (coded for by TNFRSF11B) expression is reduced by mechanical loading in osteoblasts in mice (32) , and TNFSF11/RANKL expression in osteoblasts is reportedly increased by unloading (33) . The suggestion that genetic variation in genes involved in skeletal responses to mechanical loading contribute to lumbar spine vBMD, complements findings presented by Yau et al implying that muscle loading, via paraspinal muscle function, contributes to spinal curvature (see Figure 1).…”
Section: Lumbar Spinal Volumetric Bmd; Novel Genetic Variantsmentioning
confidence: 99%
“…[32][33][34][35] It is hypothesized that such external stimuli induce interstitial fluid flow along the canaliculi, and consequently provoke shear stresses that deform the osteocyte membrane. [36,37] In response to these stimuli, osteocytes modulate the secretion of many molecules, e.g. insulin-like growth factors (IGF), osteocalcin, sclerostin, nitric oxide, RANKL, TNF-related cytokines and osteoclasts differentiation factors (ODF).…”
Section: Instructive Factors In Tissuesmentioning
confidence: 99%
“…[34][35][36][37] Through this process, osteocytes allow bone tissue adapting to external mechanical stresses by inducing osteoblasts to synthesize new bone matrix when there are increased loads, or inducing osteoclasts resorbing tissue when there is a decreased use of the bone. [34][35][36][37] Other physical triggers for remodeling are the micro-cracks that form in bone tissue due to continuous stresses during life. [137,138] In such scenario, osteocyte apoptosis occurs in proximity of the cracks.…”
Section: Instructive Factors In Tissuesmentioning
confidence: 99%
See 2 more Smart Citations